2014
DOI: 10.1136/archdischild-2014-306237.120
|View full text |Cite
|
Sign up to set email alerts
|

G120(P) Current Neonatal Resident Consultant Workforce in Level 3 NICUs in UK

Abstract: Background Peri- and postnatal events involving newborns occur 24/7 and to improve the quality of care given to this group of babies on NICUs, there has been calls from, Academy of Royal Medical Colleges, RCPCH, BAPM, government (DoH Neonatal Toolkit) to add on or augment the tier 3 level medical staffing out-of-hours leading to a consultant-delivered type of service. This has also become necessary to help plug the shortage in tier 2 medical staffing as a result of the MMC agenda and EWTD. The provision of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Similar recommendations have been made to improve the quality of care given to infants in neonatal units by the Royal College of Paediatrics and Child Health [3] and the Department of Health [5]. Although, these recommendations have been in place for a number of years and in the recent years some units in the United Kingdom have introduced resident consultant cover, the effect of this intervention on neonatal outcomes has not been evaluated in the UK [6]. Studies from Australia [7] and Canada [8] have reported no significant differences in neonatal or neurodevelopment outcomes at three years of age, but the studies were relatively small and their results might not be directly applicable to a different health system.…”
Section: Introductionmentioning
confidence: 99%
“…Similar recommendations have been made to improve the quality of care given to infants in neonatal units by the Royal College of Paediatrics and Child Health [3] and the Department of Health [5]. Although, these recommendations have been in place for a number of years and in the recent years some units in the United Kingdom have introduced resident consultant cover, the effect of this intervention on neonatal outcomes has not been evaluated in the UK [6]. Studies from Australia [7] and Canada [8] have reported no significant differences in neonatal or neurodevelopment outcomes at three years of age, but the studies were relatively small and their results might not be directly applicable to a different health system.…”
Section: Introductionmentioning
confidence: 99%